Types of Sedentary Behavior and Risk of Cardiovascular Events and Mortality in Blacks: The Jackson Heart Study. Issue 13 (2nd July 2019) - Garcia, Jeanette M.; Duran, Andrea T.; Schwartz, Joseph E.; Booth, John N.; Hooker, Steven P.; Willey, Joshua Z.; Cheung, Ying Kuen; Park, Chorong; Williams, Stephen K.; Sims, Mario; Shimbo, Daichi; Diaz, Keith M.
Abstract : Background: Previous cross‐sectional studies have shown conflicting results regarding the effects of television viewing and occupational sitting on cardiovascular disease (CVD) risk factors. The purpose of this study was to compare the association of both television viewing and occupational sitting with CVD events and all‐cause mortality in blacks. Methods and Results: Participants included 3592 individuals enrolled in the Jackson Heart Study, a community‐based study of blacks residing in Jackson, Mississippi. Television viewing (<2, 2–4, and >4 h/day) and occupational sitting (never/seldom, sometimes, often/always) were self‐reported. Over a median follow‐up of 8.4 years, there were 129 CVD events and 205 deaths. The highest category of television viewing (>4 h/day) was associated with a greater risk for a composite CVD events/all‐cause mortality end point compared with the lowest category (<2 h/day; hazard ratio, 1.49; 95% CI, 1.13–1.97). In contrast, the highest category of occupational sitting (often/always) was not associated with risk for a composite CVD events/all‐cause mortality end point compared with the lowest category (never/seldom; hazard ratio, 0.90; 95% CI, 0.69–1.18). Moderate‐to‐vigorous physical activity moderated the association of television viewing with CVD events/all‐cause mortality such that television viewing was not associated with greater risk among those with high moderate‐to‐vigorous physical activity levels. Conclusions: Television viewing was associated with greater risk of CVD events and all‐cause mortality, while occupational sitting had no association with these outcomes. These findings suggest that minimizing television viewing may be more effective for reducing CVD and mortality risk in blacks compared with reducing occupational sedentary behavior.